Literary Elements in Panyandra Traditional Javanese Bride in Surakarta Style - Vita Listiani; Darmarajah Nadarajah; Sumangala Sumangala; Songgot Paanchiangwong; Siti Rabeah Masri (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify and describe the types and functions of literary elements (unsur susastra) present in the panyandra (narrative speeches) of Surakarta-style Javanese traditional wedding ceremonies. Methodology: This descriptive study analyzed written data from the books Gita Wicara Jawi and Tuntunan Kagem Para Panatacara Tuwin Pamedhar Sabda, along with audio and video recordings of wedding narrations. Data were collected through listening, reading, note-taking, and analyzed using stylistic analysis and semantic validity with expert judgment. Main Findings: The study identified ten types of literary elements used in the panyandra, including tembung saroja, tembung garba, kerata basa, paribasan, pepindhan, candra, purwakanthi, and basa rinengga. These elements serve seven language functions: personal, instrumental, interactional, regulatory, representational, heuristic, and imaginative. Novelty/Originality of this study: This research provides the first detailed analysis of literary elements within Surakarta-style Javanese wedding panyandra, offering new insights into their aesthetic and cultural functions, which can enhance appreciation and serve as a reference for event narrators (pranata adicara) and cultural preservation efforts.